The Effect of Computer Simulation on Student Performance in High School Chemistry Learning on Chemical Equations - Ibitomi, Oluyemi Olasumbo; Oyelekan, Oloyede Solomon; Olorundare, Adekunle Solomon (Indonesian Journal of Science and Mathematics Education, 2022)
Chemical equations have been identified as a complicated topic in the Nigerian School Certificate. This study investigates the effect of computer simulations on student performance in high school chemistry courses on the topic of chemical equations in Offa, Nigeria. This study adopted a quasi-experimental research design with a pre-test, post-test, and non-randomized control group. The population is all high school students totaling 756 students. The sample was selected purposively, namely 136 students. Chemical Equation Performance Test (CEPT), Online Computer Simulation of Chemical Equations (OCSCE), and Cognitive Force Checklist (CSC) with reliability coefficients of 0.76, 0.81, and 0.78, respectively, were used as instruments for the study. The results of this study are that there are differences in the performance of students who are taught using computer simulations, between the performance of male and female students, and differences in performance between students who score low, medium, and high. It was concluded that computer simulation affected the performance of high school students. It was supposed that computer simulation affected the performance of high school students. It is recommended that future researchers apply computer simulations to other learning.